FOLK KNOWLEDGE: EPISTEMOLOGICAL VALIDITY AND SUSTAINABILITY (CIPEEX, 2026)
This article aims to show that traditional knowledge is valid and fruitful, highlighting its importance for realisticsustainability that includes Brazil’s social and economic aspects. The study explores dialogues between diversetypes of knowledge and seeks to understand the epistemological specificities of traditional communities and how they interact with their environment. It also investigates how law can contribute to protecting these communities knowledge and ways of life. The methodology combines literature review and statistical data analysis. The research points out the scarcity of in-depth epistemological approaches that consider non-Western worldviews, as well as the inefficiency of public policies in addressing the needs of these groups. Such sh ortcomings may worsen thevulnerability of traditional populations. To achieve true sustainability, it is essential to consider the characteristicsof each territory and its people. Recognizing and integrating traditional knowledge into broader sustainability strategies is crucial for building environmentally responsible and socially inclusive solutions.
Keywords: Epistemology; traditional people; ecology